1993
DOI: 10.1093/jmedent/30.5.922
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Feeding Patterns of Aedes aegypti (Diptera: Culicidae) Collected in a Rural Thai Village

Abstract: Aedes aegypti (L.) were collected by aspiration once each week from in and around houses in a rural village in Chachoengsao Province. Thailand, during May 1990 to June 1991. Of the 1,230 specimens analyzed with a sandwich ELISA, 73% reacted to one or more of the seven hosts which we tested. Eighty-eight percent (789/896) of all detectable meals were identified as being from a single host (human). Patent multiple meals (double and triple), of which one was always human, were detected in 7% (66/896) of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 0 publications
4
148
0
3
Order By: Relevance
“…The duration of the extrinsic incubation period would be set at 10 days 23 . Mosquito bites per day were set at 3 27 , and since 90% of feeds are usually taken on humans 28 , the human biting rate per day would be 2.7 12,25 . In the present report, vector capacity was simulated using the survival rates estimated by captures done with MosquiTRAP and aspirator.…”
Section: Vectorial Capacity and Basic Reproductive Numbermentioning
confidence: 99%
“…The duration of the extrinsic incubation period would be set at 10 days 23 . Mosquito bites per day were set at 3 27 , and since 90% of feeds are usually taken on humans 28 , the human biting rate per day would be 2.7 12,25 . In the present report, vector capacity was simulated using the survival rates estimated by captures done with MosquiTRAP and aspirator.…”
Section: Vectorial Capacity and Basic Reproductive Numbermentioning
confidence: 99%
“…1,2 This day-biting mosquito has a close association with the urban environment, 3,4 almost exclusively feeding on human hosts 5,6 and breeding in artificial containers found in the domestic setting (i.e., pot plant bases, tires, roof gutters, etc.). 7 Aedes aegypti regularly take multiple blood meals, often from different humans, to complete their gonotrophic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti females demonstrated that 88% of all detectable meals were identified as being from a single host (human) and only 7% of all the females had taken multiple meals (Scott et al, 1993). Engorged females in Thailand revealed that half to one-third imbibed two or more blood meals in a 36-hour time period.…”
Section: Physiology Of Reproductionmentioning
confidence: 99%
“…They are commonly found indoors, breeding in artificial containers, with female needing to feed on blood to produce eggs, as described above. Studies have demonstrated high anthropophily, with over 90% of the ingested blood being human, and the rest from pets, such as dogs and cats (Scott et al, 1993). Multiple feeding in a gonotrophic cycle can increase the risk of disease transmission by increasing the frequency of contact with hosts (Garrett-Jones, 1964;Garrett-Jones and Shidrawi, 1969;Dye, 1986).…”
Section: Life History Traits and Fitnessmentioning
confidence: 99%
See 1 more Smart Citation